THE INFLUENCE OF SOCIAL MEDIA ON PERCEPTIONS OF SUCCESS AMONG MODERN WOMEN - Quyen Do, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Social media has become an integral aspect of modern society, profoundly influencing how individuals perceive success and navigate their professional and personal lives. This article explores the complex relationship between social media and the success of contemporary women, examining both the positive and negative impacts of social media usage on women's perceptions of success, self-esteem, and well-being. Drawing on a synthesis of existing literature, empirical research, and real-life examples, we delve into the ways in which social media platforms shape societal norms, cultural values, and individual aspirations, particularly among women. We discuss the role of social media in perpetuating unrealistic beauty standards, fostering comparison culture, and exacerbating feelings of inadequacy and self-doubt. Conversely, we highlight the empowering potential of social media as a tool for self-promotion, networking, and community-building, enabling women to challenge stereotypes, amplify their voices, and pursue their passions. Furthermore, we propose strategies for harnessing the positive effects of social media while mitigating its negative consequences, including promoting authenticity, fostering digital literacy, and advocating for policy changes. Finally, we identify avenues for further research to deepen our understanding of the nuanced interplay between social media and women's success, emphasizing the importance of interdisciplinary collaboration and ethical considerations in studying this complex phenomenon. By engaging in dialogue, research, and action, we can cultivate a digital landscape that empowers women to thrive, succeed, and authentically express themselves in the 21st century.